Knowledge Level about Thalassemia among High School Students in Pontianak City, West Kalimantan, Indonesia - Noeriman, Aisya Rezki; Fitrianingrum, Iit; Armyanti, Ita (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Thalassemia is a genetic disorder that affect the formation of hemoglobin and has high prevalent in Indonesia. Awareness of genetic screening as one of steps to prevent thalassemia require adequate knowledge about thalassemia. There is no data refers to knowledge about thalassemia among high school student in Pontianak City meanwhile that data is important as initial data to planning thalassemia prevention program. Objective: This study assessed knowledge about thalassemia among high school students in Pontianak City. Method: This descriptive study assessed 100 high school students in Pontianak City chosen by propotionated stratified random sampling according to the number of high school students in each district. Result: Most respondents have poor knowledge about thalassemia (49%) with more female students have good knowledge (27,1%) than male students (10%). Sources of information used by respondents are internet (44%), school (17%), health workers (17%), seminars (10%), relatives/friends (6%), and print media (6%). Conclusion: Many high school students in Pontianak City has poor knowledge about thalassemia (49%) therefore spreading information about thalassemia is essential to be done through the most information source that used by students which is internet (44%) or health education program with school and health workers are involved (17%).